2005
DOI: 10.1161/01.atv.0000183745.37161.6e
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid–Induced Heme Oxygenase-1 Expression Is Mediated by Nuclear Factor Erythroid 2-Related Factor 2 and p38 Mitogen-Activated Protein Kinase in Human Monocytic Cells

Abstract: These results demonstrate that ALA induces HO-1 expression in THP-1 monocytic cells via Nrf2 and p38. Further studies are required to investigate whether the protective effects of ALA in monocytes are mediated by HO-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 46 publications
7
60
0
Order By: Relevance
“…Our results also suggested that inhibition of HO-1, Hsp72, or iNOS proteins by the inhibitors ZnPP IX, quercitin, or L-NMMA, respectively, abrogated the protective effect of 75 μM ALCAR+50 μM LA (data not shown), demonstrating that HO-1 or Hsp72 or iNOS are likely involved in the ALCAR+LA-mediated cytoprotection against HNE-induced oxidative stress. It has been recently demonstrated that LA induces HO-1 expression in THP-1 monocytic cells via Nrf2 and p38 (72). Our results are consonant with the recent studies, which shows that ALCAR is cytoprotective against inflammatory and oxidative insults in astrocytes in part by being able to up-regulate cytoprotective cellular stress responses, particularly induction of HO-1, while inhibiting induction of iNOS (73).…”
Section: Discussionsupporting
confidence: 92%
“…Our results also suggested that inhibition of HO-1, Hsp72, or iNOS proteins by the inhibitors ZnPP IX, quercitin, or L-NMMA, respectively, abrogated the protective effect of 75 μM ALCAR+50 μM LA (data not shown), demonstrating that HO-1 or Hsp72 or iNOS are likely involved in the ALCAR+LA-mediated cytoprotection against HNE-induced oxidative stress. It has been recently demonstrated that LA induces HO-1 expression in THP-1 monocytic cells via Nrf2 and p38 (72). Our results are consonant with the recent studies, which shows that ALCAR is cytoprotective against inflammatory and oxidative insults in astrocytes in part by being able to up-regulate cytoprotective cellular stress responses, particularly induction of HO-1, while inhibiting induction of iNOS (73).…”
Section: Discussionsupporting
confidence: 92%
“…It is essential to determine whether their stimulatory effect on insulin signaling is dependent on Nrf2 activity. Again, the Nrf2 null mice will be the asset for these studies; (4) The AMP-dependent kinase activator metformin, PPARγ agonists and α-folic acid were shown to improve glucose control and also to attenuate oxidative stress [101][102][103][104] . Whether these existing drugs exert these effects via Nrf2 activation requires further investigations; and (5) Nrf2 can upregulate CD36 expression involved in lipid uptake.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its substrate heme, a variety of conditions and agents, both physiologic and nonphysiologic, including UV irradiation, hyperthermia, inflammatory cytokines, bacterial endotoxins, and heavy metals, potently stimulate HO-1 (16)(17)(18)(19)(20). This is due to the 5′-flanking region of the HO-1 gene containing binding sites for several different transcription factors that regulate inflammation and apoptosis, including NF-κB, activator protein-1 (AP-1), and NF-E2-related factor 2 (Nrf2; refs.…”
Section: Introductionmentioning
confidence: 99%